APPLYING FORENSIC PSYCHOLOGY PRINCIPLES TO CHILD BEHAVIOR ASSESSMENT AND EARLY INTERVENTION - Lucy Lidiawati Santioso; Livia Alves; Bruna Costa (Yayasan Adra Karima Hubbi, 2026)
Early identification of behavioral risk in children is essential for preventing the escalation of developmental, emotional, and social difficulties. Conventional child behavior assessment practices, however, often rely on fragmented observations and subjective judgments that may overlook contextual risk factors. Applying forensic psychology principles offers a structured and evidence-based framework that emphasizes systematic observation, behavioral pattern analysis, and contextual interpretation. This study aims to examine the applicability and effectiveness of forensic psychology principles in child behavior assessment and early intervention contexts. The research employed a qualitative-dominant mixed-methods design involving structured behavioral observations, semi-structured interviews with educators and practitioners, and analysis of assessment records in educational and community-based settings. The findings indicate that forensic-informed assessment enhances the accuracy of early behavioral risk identification and supports more targeted and timely interventions. Children assessed using this framework demonstrated greater behavioral improvement following early intervention, particularly in emotional regulation and social interaction. The results also highlight that behavioral difficulties are closely linked to environmental and contextual factors rather than fixed individual deficits. The study concludes that forensic psychology principles can be effectively adapted beyond legal contexts to support preventive, ethical, and developmentally sensitive child behavior assessment. Integrating these principles into early intervention practices strengthens interdisciplinary collaboration and contributes to more responsive support systems for children at behavioral risk.